MORPHOMETRIC CHARACTERISTICS OF THE MANDIBULAR CONDYLAR PROCESSES - Hadi, Darawsheh; Sergey, Dydykin; Aisr, Zmiro; Sergey, Gupalo; Marina, Kapitonova; Gurgen, Pakhlevanyan; Elizaveta, Terekhina; Natalya, Tiunova; Viktoria, Vladimirova; Emin, Mammadov; Yuriy, Vasilev (European Scientific Society (e.V.), 2023)
Aim: to study the morphometric characteristics of the mandibular condylar processes to identify patterns and their classification. Materials and Methods: a study of 49 skeletonized and certified mandibular preparations was performed using a caliper and a depth gauge. During the study of the material, the forms and the main morphometric parameters of the condylar processes were determined and analyzed. Statistical data processing was carried out using the Microsoft Excel program. Results: The study of certified biological material yielded the main morphometric and morpho functional parameters of the mandibular condylar processes. We revealed characteristic differences in the anatomical structures of the studied preparations. The main variants and types of combinations of forms of condylar processes were singled out: oval, hook-shaped, diamond-shaped, L-shaped. The lowest asymmetry index is characteristic of a combination of oval and diamond–shaped forms - 2.44%., and the highest asymmetry index is characteristic of diamond–shaped and L-shaped forms of condylar processes - 7.13%. Conclusion: The presented data can help practitioners to more accurately determine the target point for Gow-Gates anesthesia; to take into account the nature of the influence of structural changes in the joint on other elements of the dental apparatus, thus preventing functional diseases of the temporomandibular joint. The methodology of studying the main morphometric parameters on skeletonized preparations of the lower jaws can be adapted for the examination of living persons using diagnostic radiology.